Insights From the Analysis of Clinicopathological and Prognostic Factors in Patients With Gallbladder Cancer - Wu, Di; Jin, Wenjian; Zhang, Yue; An, Yong; Chen, Xuemin; Chen, Weibo (Frontiers in Oncology, 2022)
Aims: To investigate the clinical efficacy and prognostic factors of primary gallbladder cancer (GBC) treated by radical surgery. Methods: The clinical and pathological data of 168 patients with primary gallbladder cancer admitted and treated in the Third Affiliated Hospital of Soochow University from January 1st，2010 to December 31st，2018 were analyzed retrospectively. Kaplan Meier method was used to draw the survival curve and evaluate the survival rate. Chi-square test was used for univariate analysis and binary logistic regression was used for multivariate analysis. Results: 94 cases showed symptoms of abdominal pain and abdominal distension. 7 cases showed symptoms of fatigue and weight loss. Jaundice occurred in 10 patients. Fever occurred in 6 patients. 51 patients had no symptoms at all. The median survival time of 168 patients was 35.0 (1.0 ~ 142.0) months. The overall 1-, 2- and 3-year cumulative survival rates were 69.6%, 55.4% and 48.8% respectively. The univariate analysis indicated that preoperative bilirubin, tumor size, tumor location, pathological type, degree of differentiation, liver invasion, nerve invasion, vascular invasion, surgical margin, filtration depth and N staging were significant factors influencing prognosis of patients with primary GBC (P<0.05). The results of multivariate analysis demonstrated that degree of differentiation, nerve invasion, filtration depth and N staging were independent risk factors for prognosis of patients with primary GBC (P<0.05). Conclusion: Patients with risk factors of gallbladder cancer should be more active in early cholecystectomy to avoid the malignant transformation of benign diseases. Degree of differentiation, nerve invasion, filtration depth and N staging were important factors for poor prognosis of patients with primary GBC. For T4 staging patients, preoperative evaluation should be more comprehensive, and patients and surgeons should be more prudent in adopting appropriate clinical treatment. The primary purpose should be prolonging the survival time and improving the quality of life.